46 Sandwich-type ethylcellulose films for controlled release of anti-restenosis drugs. (19th December 2016) - Wang, Liying; Jin, Yuanbao; Jin, Yuanyuan; Zhao, Mingzhi; Liu, Yumeng; Meng, Fanxin
Abstract : Objectives: Restenosis is a response of the vessel wall to balloon-induced injury and is characterized primarily by elastic recoil of the vessel wall and a series of pathological processes including thrombus, inflammation and vascular smooth muscle cell (VSMC) proliferation. To treat restenosis, appropriate drug delivery vehicles are needed which can release therapeutic agents targeting different symptoms into blood vessels in a controlled manner. The main objective of the present study was to prepare sandwich-type ethyl cellulose films with high performance for efficient drug loading and controlled drug release for restenosis treatment. Methods: Sandwich-type ethyl cellulose films loaded with probucol for treating coronary artery disease, or aspirin as an antithrombotic drug, were prepared by casting three individual layers in sequence using an ethyl cellulose/toluene solution. On a glass plate, the first ethyl cellulose layer (bottom layer) was cast without drugs, on to which the middle layer containing probucol or aspirin was then cast. After solvent evaporation at room temperature, a third top layer was cast on to the middle layer. The obtained drug-loading films were further dried at room temperature under vacuum. Results: The sandwich-type ethyl cellulose films exhibited a drug loading content (DLC) of 12.1 ± 0.9% and a drug loading efficiency (DLE) of 73.5 ± 3.6% for aspirin, and a DLC of 11.0 ± 0.8% and a DLE of 69.3 ± 3.4% for probucol. Under physiological conditions (37°C, pH 7.4), the release half-life of aspirin from the films was 2.7 ± 0.2 hours, while that of probucol was 7.1 ± 0.6 days. The two drugs showed totally different release behaviors, which can be employed in combination to treat restenosis. Conclusion: Sandwich-type ethylcellulose films loaded with probucol or aspirin were successfully prepared and showed ability to release the two drugs in different ways: rapid release of aspirin to treat thrombus and inflammation typical of early-stage restenosis, and sustained release of probucol for inhibition of VSMC proliferation frequently seen in the later stage of restenosis. These drug-loaded ethylcellulose films provide new insight into restenosis therapy.